2019
DOI: 10.1371/journal.pone.0222037
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic cost calculations of gait using musculoskeletal energy models, a comparison study

Abstract: This paper compares predictions of metabolic energy expenditure in gait using seven metabolic energy expenditure models to assess their correlation with experimental data. Ground reaction forces, marker data, and pulmonary gas exchange data were recorded for six walking trials at combinations of two speeds, 0.8 m/s and 1.3 m/s, and three inclines, -8% (downhill), level, and 8% (uphill). The metabolic cost, calculated with the metabolic energy models was compared to the metabolic cost from the pulmonary gas exc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 45 publications
8
59
0
Order By: Relevance
“…Although all modeling combinations produced the positive or negative trends relative to published data, not all of them resulted in slopes that were statistically similar to those found in the literature. This finding is similar to a recent study by Koelwijn et al (Koelewijn et al, 2019), where several metabolic cost models (including U03 and B04) were shown to predict the correct trends for CoT as a function of walking slope or gait speed in accordance to trends found in the literature (Margaria, 1968). Additionally, Koelwijn et al (Koelewijn et al, 2019) found that B04 tended to underestimate CoT values in comparison to experimental values, which is in agreement with our findings.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Although all modeling combinations produced the positive or negative trends relative to published data, not all of them resulted in slopes that were statistically similar to those found in the literature. This finding is similar to a recent study by Koelwijn et al (Koelewijn et al, 2019), where several metabolic cost models (including U03 and B04) were shown to predict the correct trends for CoT as a function of walking slope or gait speed in accordance to trends found in the literature (Margaria, 1968). Additionally, Koelwijn et al (Koelewijn et al, 2019) found that B04 tended to underestimate CoT values in comparison to experimental values, which is in agreement with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Bhargava's model needed muscle specific tension to be around 37 N/cm 2 rather than 61 N/cm 2 to match experimental averages the best. This new value is closer to values used within OpenSim (Delp et al, 2007) and studies such as (Miller, 2014;Koelewijn et al, 2019). Future work to optimize muscle specific tension could improve the magnitude of CoT predictions (Hamner and Delp, 2013;Uchida et al, 2016a;Falisse et al, 2019).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…2-b). Hill-type muscle models can be used with models of metabolic energy consumption [21,22,23] and muscle fatigue [24,25,26] to estimate these quantities in simulations. Musculoskeletal parameter values are determined for average humans based on measurements from a large number of people and cadavers [27,28,29,30] and can be customized to match an individual's height, weight, or CT and MRI scan data [31,32].…”
Section: Musculoskeletal Simulationsmentioning
confidence: 99%